Adaptation of Co-Cr copings made by induction casting and selective laser melting in CAD/CAM with clinical scanning - Spoljaric Muñoz, María Alejandra (2020)
The technique of lost wax cast by induction centrifugation (CPCI) and selective laser fusion (SLM) in design and computer- aided manufacturing (CAD / CAM) with clinical scanning, are techniques for manufacturing cobalt-chromium copings (Co-Cr), have diﬀerent production processes. Objective: To evaluate, in vitro, the marginal and internal adaptation of Co- Cr metal copings made on a chamfer termination line with the CPCI and SLM technique in CAD / CAM with clinical scanning. Material and Methods: A master model of Co-Cr premolar shape was made in CAD / CAM with chamfer termination line. With a clinical scanner, the master model was scanned and 13 Co-Cr copings manufactured in SLM were obtained. Impressions were taken to obtain models in type IV plaster where 13 Co-Cr copings with CPCI technique were manufactured. The marginal and internal adaptation was evaluated using the silicone replica technique, the samples were divided into segments: vestibulo-palatal and mesio-distal and were evaluated by stereo microscope. Results: The marginal and internal discrepancies were lower for the CPCI group compared to the SLM technique in CAD / CAM with clinical scanning. In addition, the results obtained for the marginal adaptation were less than 120 μm and the internal adaptation less than 350 μm for both techniques. Conclusions: The marginal and internal adaptation in the CPCI technique compared to SLM in CAD/CAM with clinical scan were better with statistically signiﬁcant diﬀerence (p <0.05). In addition, the results obtained were within the clinically acceptable paramenters.